Implementação de um sistema de custeio por actividades ao episódio numa organização hospitalar - Silva, Claudia Nunes Ferreira da (2013)
Health spending in Portugal, as well as in other EU and OECD countries, has grown at a faster rate than economic growth, thus assuming increasing importance in GDP. This systematic growth of health spending and hospitals costs diverted attention from the need to raise funds for the sector, to focus on the question of efficient allocation. Hence the growing interest in the study of hospitals production and costs, crucial for their management. This thesis aims to determine the role of activity-based costing as an increasingly relevant measure to hospitals cost management and as means to increase hospital efficiency, supported by its application to a large Portuguese hospital. This method helps in analysing the cost and operational efficiency, decision making and minimizing distortions in indirect costs allocation to services, which can and should be used as a tool of daily administration. It is also crucial in awareness of the costs involving the various hospital activities. Despite the difficulties that the implementation of an activity-based costing system might imply, is was concluded that this system has many advantages for the knowledge of the hospital’s costs. The hospital knows the costs incurred by business as well as areas where efficiency can be improved, leading to practice restructuring. The system also provides solid information about the cost of production, useful to renegotiate contracts. The main disadvantages verified were the length, cost and complexity of costing the patient, therefore future iterations will only calculate the average cost.